1048Characteristics of ST-Elevation Myocardial Infarction (STEMI) patients in Asia Pacific: findings from the ASPECT collaboration. (2nd September 2021) - Chih, HuiJun; Brennan, Angela; Yeo, KK; Chan, Mark; Yan, Bryan; Duffy, Stephen; Nguyen, Hoai; Loi, Do Doan; Fong, Alan; Reid, Christopher
Abstract: Background: The Asia Pacific Evaluation of Cardiovascular Therapies (ASPECT) Collaboration was established to better understand the characteristics of patients undergoing PCI and cardiac interventions across the Asia Pacific region, including STEMI. The aim of this study was to compare STEMI patient characteristics across Asia Pacific (AP) countries in order to understand regional differences. Methods: Each site across Australia, Singapore, Malaysia, Vietnam and Hong Kong provided de-identified individual patient data. Comparison of characteristics by sites were performed using one-way ANOVA, Kruskal-Wallis or Chi-squared tests, using Stata 14.2. Results: Of the 12, 620 cases, there were more males (p < 0.001) and the average of patients' age ranged from 55 (Malaysia) to 68 (Vietnam) years old. Family history of coronary artery disease was not common amongst Hong Kong (1%) and Singaporean (12%) patients, and most patients did not have history of congestive heart failure, peripheral vascular disease or coronary artery bypass grafting. History of dyslipidaemia varied significantly among patients in Malaysia (98%) and Vietnam (12%) (p < 0.001). About 37% of the Malaysian patients had previous myocardial infarction, which is greater than twice of other cohorts (p < 0.001). Most cohort had either normal or mild ejection fraction (EF) but 40% of the Singaporean patients had severely reduced EF (p < 0.001). Conclusions: Patient characteristics varied significantly across AP countries. On-going analyses will focus on the impact of varying patient characteristics on clinical outcomes. Key messages: As characteristics varied, prevention and procedural strategies need to be adapted carefully. Additional input from other AP countries will better inform these strategies.